Cord blood myostatin concentrations by gestational diabetes mellitus and fetal sex - Huang, Rong; Kibschull, Mark; Briollais, Laurent; Pausova, Zdenka; Murphy, Kellie; Kingdom, John; Lye, Stephen; Luo, Zhong-Cheng (Frontiers in Endocrinology, 2023)
Myostatin is a member of the transforming growth factor β superfamily, and is mainly secreted from skeletal muscle. Animal studies have demonstrated that deficiency in myostatin promotes muscle growth and protects against insulin resistance. In humans, gestational diabetes mellitus (GDM) impairs fetal insulin sensitivity. Females are more insulin resistant and weigh less than males at birth. We sought to assess whether cord blood myostatin concentrations vary by GDM and fetal sex, and the associations with fetal growth factors. This was a study of 44 GDM and 66 euglycemic mother-newborn dyads. Myostatin, insulin, proinsulin, insulin-like growth factor (IGF)-1, IGF-2 and testosterone were measured in cord blood samples. Cord blood myostatin concentrations were similar in GDM vs. euglycemic pregnancies (mean±SD: 5.5±1.4 vs. 5.8±1.4 ng/mL, P=0.28), and were higher in males vs. females (6.1±1.6 vs. 5.3±1.0 ng/mL, P=0.006). Adjusting for gestational age, myostatin was negatively correlated with IGF-2 (r=-0.23, P=0.02), but not correlated with IGF-1 (P=0.60) or birth weight (P=0.23). Cord blood myostatin was strongly correlated with testosterone in males (r=0.56, P<0.001), but there was no correlation in females (r=-0.08, P=0.58) (test for difference in r, P<0.001). Cord blood testosterone concentrations were higher in males vs. females (9.5±6.4 vs. 7.1±4.0 nmol/L, P=0.017), and could explain 30.0% (P=0.039) of sex differences in myostatin concentrations. The study is the first to demonstrate that GDM does not impact cord blood myostatin concentration, but fetal sex does. The higher myostatin concentrations in males appear to be partly mediated by higher testosterone. The findings shed new light on developmental sex differences in insulin sensitivity regulation relevant molecules in early life.